Meningkatkan Hasil Belajar IPA Menggunakan Model Project Team di Kelas 5 Sekolah Dasar - Nadia; Mahmuddin (CV. ITTC INDONESIA, 2023)
The problem in learning science in grade 5 UPTD SDN 2 Kait-Kait is the lack of student activity and student learning outcomes. This is because learning is still one-way, learning tends to be boring and less interesting and the learning atmosphere is less pleasant. Thus, it is necessary to innovate learning by combining several learning models into the Project Team learning model. The purpose of this study is to analyze how student activity and analyze the improvement of student learning outcomes. This research uses a qualitative approach with the type of Classroom Action Research (PTK) which is carried out in 3 meetings. The results showed that student activity reached a percentage of 92% with the criteria of